Donald Judd : Architecture . - Österreichisches Museum für angewandte Kunst, Wien (Ostfildern-Ruit : Hatje Cantz Verlag, 2003)
All facets of Judd's work converge in Marfa, West Texas, where he systematically turned an abandoned fort into one of the world's major ensembles of contemporary art. This book uses drawings, plans, and photographs of Marfa ro illustrate Judd's radical approach to architecture and design, and to demonstrate the meticulous attention he paid to the settings for his installations. Photographs of Judd's aluminium and wooden furniture series and examples of his pywood tables, chairs, and shelves display his stringent application of aesthetic brevity and precision in form and material.
Donald Judd was one of the leading artists of the second half of the twentieth century. His "specific objects" - which he refused to call sculpture - represent a radical and revolutionary use of space, scale, and materials. By contrast, the primary concern in his many drafts and designs for architecture and furniture is utility, although the formal relationship to his artistic objects is plain.
First published in German in 1991, this revised and expanded edition contains additional illustrations and several essays that have not previously appeared in English. Judd's original contribution, an anti-war essay written during the 1991 Gulf War, is complemented by a second essay on the relationship between art and architecture.
biog. p.136-138
Duits
Engels
Donald Judd : Architecture = Architektur, Österreichisches Museum für angewandte Kunst / Gegenwartskunst, Wien, February 14 - April 8, 1991
boek
Keywords: Judd, Donald